Community-based integration of management of non-communicable diseases in China - Yue Xiao (KeAi Communications Co., Ltd., 2015)
Non-communicable diseases (NCDs) are a leading cause of deaths and of disease burden in China. This paper analyzes the rationale and implications of a community-based approach to a better coordinated NCDs care and management system in China. As argued by the author, the buildup of an integrated NCDs care delivery system is feasible now and large health expenditures will be saved if more stable outpatients with NCDs could be shifted to community health facilities to receive their medications. However, the key issues remain in building a general practitioner led (GP-led) primary care delivery system in China. Some prominent issues include the shortage of quality generalists, lack of proper incentives and management mechanisms, and the absence of patients and provider, and restrictive arrangements in basic health insurance policies. Even with these hard-to-solve issues, some recent reform initiatives for integrated NCDs care delivery in some localities have demonstrated originality and creativeness in developing better coordination between primary and secondary NCDs care. However, without large-scale public sector reform, innate issues with human resource development, income distribution and financing of public healthcare providers cannot be solved. It may take a long time to see deep integration of primary and secondary NCDs care in China. Keywords: Non-communicable disease, Integrated managements, Coordination